A Blockchain-based framework for secure Educational Credentials (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain provides a creative approach to storing information, executing transactions, conducting tasks, and building trust. Some see Blockchain as a revolutionary technology for cryptography and cybersecurity, with applications ranging from cryptocurrency to healthcare, smart contracts, Internet of Things, smart grids governance, supply-chain etc. This research work would offer a detailed analysis of blockchain Security, Privacy and Trust. It further studies the applications of blockchain technology in the domain of education and involved challenges. Finally, it proposes a blockchain-based framework for secure and reliable student's record management.